Andrzej Zwoliński, Dylematy demokracji, Wydawnictwo WAM, Kraków 2010, ss. 248. - Kamińska, Agnieszka (Przegląd Politologiczny, 2018)
Andrzej Zwoliński, Dylematy demokracji, Wydawnictwo WAM, Kraków 2010, ss. 248.